Social Dynamics in Arabic Language Learning at Al-Azhar Course Pare - Nabiilah, Alaikin; Hafidz, Abdurrahman; Wijayanto, Ryan Wahyu; Uqba, M Sholih Salimul (UMSU, 2024)
The aim of this research is to analyze the social dynamics of Arabic language learning at the Al-Azhar Course. This type of research is qualitative research with descriptive methods. This research tries to solve the problem by describing the problems that occur. This is based on the consideration that the researcher wants to understand and study in depth and explain the social dynamics in Arabic language learning by focusing on data that refers to the disclosure of what the resource person said and then collects it in explanatory words and not in the form of numbers. The research results show that there are three aspects of social dynamics that occur in the Arabic language learning process at the Al-Azhar Pare Course Institute, namely; a) Communication aspect, interaction between students and teachers takes place smoothly and effectively. b) Collaboration aspect, students and teachers work together to achieve learning goals, c) Mutual respect aspect, it can be seen that students and teachers have an attitude of mutual respect.